2001
DOI: 10.1097/00004872-200109000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous angiotensin II suppresses insulin signaling in vascular smooth muscle cells from spontaneously hypertensive rats

Abstract: These results indicate that endogenous Ang II suppresses insulin signaling in VSMC from SHR by activating extracellular signal-regulated kinase. These findings suggest that tissue Ang II may play a role in insulin resistance in hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 20 publications
3
33
0
1
Order By: Relevance
“…This suggests that normal growth of intestinal muscularis is regulated by other IRS-1-linked hormones than IGF-I, which could include growth hormone and angiotensin II, which both have trophic effects on smooth muscle and both activate IRS-1 (6,17).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that normal growth of intestinal muscularis is regulated by other IRS-1-linked hormones than IGF-I, which could include growth hormone and angiotensin II, which both have trophic effects on smooth muscle and both activate IRS-1 (6,17).…”
Section: Discussionmentioning
confidence: 99%
“…Ang II has been found to attenuate or inhibit insulin signalling in vascular smooth muscle cells (Vellosa et al 1996, Folli et al 1997, Fukuda et al 2001, implicating a role for the RAS in regulating the actions of insulin. Recent experiments have shown that Ang II is a potent inducer of renal oxidative stress, both in vivo and in vitro (Hannken et al 1998, James et al 1998, Haugen et al 2000.…”
Section: Discussionmentioning
confidence: 99%
“…The overactivity of the RAS is likely to impair insulin signaling and contribute to the insulin resistance observed in essential hypertension [7]. Accordingly, the activation of the RAS was shown to modulate muscle insulin signaling, leading to a decrease in insulin-stimulated glucose uptake [45,46]. At the molecular level, captopril improves insulin action by increasing IRS-1 tyrosine phosphorylation and association with PI 3-kinase [39].…”
Section: The Cross-talk At the Extracellular Levelmentioning
confidence: 99%